2016
DOI: 10.1109/comst.2016.2586999
|View full text |Cite
|
Sign up to set email alerts
|

Software Defined Optical Networks (SDONs): A Comprehensive Survey

Abstract: The emerging Software Defined Networking (SDN) paradigm separates the data plane from the control plane and centralizes network control in an SDN controller. Applications interact with controllers to implement network services, such as network transport with Quality of Service (QoS). SDN facilitates the virtualization of network functions so that multiple virtual networks can operate over a given installed physical network infrastructure. Due to the specific characteristics of optical (photonic) communication … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
148
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 305 publications
(150 citation statements)
references
References 451 publications
0
148
0
2
Order By: Relevance
“…bandwidth variable cross-connects or spectrum selective switches) as well as flexible control plane, are also considered essential tools. A flexible optical networking paradigm has been proposed to provide all these features and the interested reader interested can refer to [15], [20], [21] for more details. In this manuscript, we focus on flexible transceivers and the network operation aspects directly dependent/related to them.…”
Section: Reference Scenariomentioning
confidence: 99%
See 1 more Smart Citation
“…bandwidth variable cross-connects or spectrum selective switches) as well as flexible control plane, are also considered essential tools. A flexible optical networking paradigm has been proposed to provide all these features and the interested reader interested can refer to [15], [20], [21] for more details. In this manuscript, we focus on flexible transceivers and the network operation aspects directly dependent/related to them.…”
Section: Reference Scenariomentioning
confidence: 99%
“…Authors in [24] identify several transponder parameters that can be controlled, such as the line rate, modulation format, code, central frequency of the optical flows, and the association of optical transport network (OTN) streams with a specific optical flow. A review of several studies, related to the software defined optical networks (SDON), can be found in [21]. Majority of researchers use the OpenFlow protocol, in order to control and configure the physical devices.…”
Section: Sdn Control Of Optical Transceiversmentioning
confidence: 99%
“…Readers interested in a general presentation of the SDN architecture, together with a thorough survey of SDN solutions applied to optical networks, are encouraged to refer to [9].…”
Section: A Novel Taxonomy For State-of-the-art Sdn Controllersmentioning
confidence: 99%
“…In [9], the authors propose a virtual topology design and lightpath routing algorithm based on the concept of loose virtual topologies, it pluses lightpaths generated by MaxSingleHop [4] algorithm for unsatisfied traffic in the ring. In [6], the authors split the virtual topology problems into several subproblems: virtual topology design, routing for lightpaths, wavelength assignment. Although these papers focus right on the IP over WDM traffic engineering problems, but all of their algorithms are based on heuristic approaches and can't be analyzed mathematically.…”
Section: Introductionmentioning
confidence: 99%